77.8k views
1 vote
(4-2i).(6-3i) / (1-i).(1+i)

2 Answers

2 votes

Answer:

2i + 6

Explanation:

4-2 = 2

6-3 = 3

2 * 3 = 6

2i

User Stem Florin
by
4.3k points
2 votes

Answer:

9 - 12i

Explanation:

Noting that i² = - 1

Expand the factors on the numerator and denominator

(4 - 2i)(6 - 3i) = 24 - 12i - 12i + 6i² = 24 - 24i - 6 = 18 - 24i

(1 - i)(1 + i) = 1 + i - i - i² = 1 + 1 = 2

The division reduces to


(18-24i)/(2)

=
(18)/(2) -
(24)/(2) i

= 9 - 121i

User Chuck Bergeron
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.